The Eurovision Song Contest and European Television History: Continuity, Adaptation, Experimentation - Pajala Mari (Routledge, 2022)
The Eurovision Song Contest (ESC) has been a part of the European television landscape continuously from the 1950s, when television was a new medium, to the present, when television programmes are increasingly accessed on platforms other than broadcast television. As a result, it offers a unique opportunity for studying and teaching European television and media history. However, few scholars in media studies have been interested in the ESC's history. In this chapter, I explore what the history of the ESC can contribute to our understanding of media events and their historical development. I argue that the exceptional longevity of the ESC as a media event rests on continuity, adaptation as well as experimentation. Although the basic format of the ESC final has remained recognisable for decades, the programme has been continuously adapted to the changing media environment, for instance in response to changes in technology and television aesthetics. As an annual event, the ESC continues broadcast television's function of creating a shared calendar of events. At the same time, the contest's temporal form has been adapted to the current media environment, both by extending the duration of the contest and by producing short-form material that circulates online.
The Eurovision Song Contest as a Cultural Phenomenon: From Concert Halls to the Halls of Academia